Book review of the adaptable mind: What neuroplasticity and neural reuse tells us about language and cognition - Pan, Xueyao; Li, Xi (Frontiers in Neuroscience, 2022)
From Noam Chomsky to Jerry Fodor, the modularity of mind has been deeply rooted in cognitive science. From the “modular” perspective, cognition consists of functionally and anatomically isolable subsystems. Therefore, it is reasonable to assume a language module or a hardwired language organ that is functionally and anatomically different from the other cognitive modules (e.g., vision, olfaction, motor, etc.). However, evidence from neuroscience casts doubt on this modular hypothesis. It has been shown that many brain regions are likely to be reused and recycled by various neural communities in order to serve various cognitive functions. If this is the case, language and other cognitive faculties should not be modules since they cannot be realized in special-purpose, special-structure regions. Therefore, it’s time to change our understanding of our brain.